Effects of ambient pressure on ignition and flame characteristics in diesel spray combustion. (1st February 2019) - Pang, Kar Mun; Jangi, Mehdi; Bai, Xue-Song; Schramm, Jesper; Walther, Jens Honore; Glarborg, Peter
Highlights: Effects of ambient pressure ( Pam ) on spray flames are characterized. Mixture fraction during the main ignition does not vary monotonically with Pam . The main ignition shifts to the fuel-lean side in the case with the highest Pam . Factors that lead to higher soot formation rates at high Pam are identified. Abstract: This work reports on numerical investigation of effects of ambient pressure ( Pam ) on spray combustion under engine-like conditions. Three cases with different Pam of 42, 85 and 170 bar at a fixed ambient temperature of 1000 K are considered. Zero-dimensional calculations are first performed for autoignition of stagnant adiabatic homogenous mixtures to evaluate performance of the selected diesel surrogate fuel models and to identify the Pam effects on the most reactive mixture. An Eulerian-based transported probability density function model is then chosen for the three-dimensional computational fluid dynamics study. The results show the predicted ignition delay times and flame lift-off lengths are in reasonably good agreement with experiment, with the relative difference below 28%. The current work reveals that low-temperature reactions occur across a wide range of mixture fraction but a noticeable rise of temperature (>100 K above ambient temperature) is detected first on the fuel-lean side of the stoichiometric line in all three cases. The high-temperature ignition occurs first on the fuel-rich side in the 42 and 85 bar cases, where the igniting mixture appears to be more fuel-rich in the latter case. As Pam is further increased to 170 bar, the igniting mixture becomes more fuel-lean and the high-temperature ignition occurs on the fuel-lean side. The ignition behavior is found to depend on both physical and chemical processes. At 170 bar, the reaction rate increases and the associated transition from low- to high-temperature ignition is relatively fast, as compared to the transport of warmer products from the lean zone into the fuel-rich mixture. Also, within the fuel-rich region, the local temperature is low due to liquid fuel vaporization and the condition is not appropriate for ignition. These collectively cause the high-temperature ignition to occur on the fuel-lean side. Analyses on the quasi-steady spray flame structures reveal that, apart from poorer air entrainment due to reduced lift-off length, the higher rich-zone temperature and lower scalar dissipation rate also lead to a higher peak soot volume fraction at higher Pam .